Determining the criticality profile of manufacturing SMEs under the influence of internal and external factors on performance - Grosu, Veronica; Petrescu, Corina; Ciubotariu, Marius-Sorin (Journal of Business Economics and Management, 2024)
Recent economic instability has heightened the need for companies to be aware of the threats in their internal and external environments and the impact these have on their performance capacity. Thus, this paper aims to identify the most impactful factors on the performance of small and medium-sized enterprises engaged in manufacturing activities in Romania, by conducting empirical questionnaire-based research, resulting in a database with primary data to be processed. A 5-point Likert scale was used to determine the frequency of occurrence and intensity of impact of the selected factors, the level of criticality of these factors being calculated using the mean value method. The results highlight the prevalence of external factors among the top critical factors, those with the most significant impact on the performance being the high cost of raw materials, lack of professionals and specialists, fluctuations in market demand, fluctuations in government policies and legislative regulations. The usefulness of the results obtained lies in the fact that they create a risk or criticality profile of the analyzed production sector, which makes it possible to address its critical points with the most optimal solutions in the given context, on the part of both management and government, thus ensuring increased performance.